PRIMARY BREAST LYMPHOMA: A CASE REPORT - HAFEEZ, T; ATTA , MB; IMTIAZ, K; AQEEL, S; AHMED, M; ASHRAF, A; RUBEET, A; RANDHAWA, I (Biological and Clinical Sciences Research Journal, 2024)
Hematological malignancies, such as lymphomas, rarely involve breast tissues, comprising only 0.04% to 0.7% of all breast neoplasms. This rarity may be attributed to the scarcity of lymphoid tissue in the breast. Primary breast lymphomas pose a diagnostic challenge due to nonspecific imaging findings that can overlap with other breast tumors. This article provides a case study and literature review on primary breast lymphoma.